1988
DOI: 10.1016/0014-5793(88)80823-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fibroblast growth factor on phosphorylation and activity of a 34 kDa lipocortin‐like protein in bovine epithelial lens cells

Abstract: We examined the effect of basic fibroblast growth factor (FGF) on phosphorylation and lipocortin-like activity of the 34 kDa protein present in the basal membrane of epithelial peripheral cells which initiate growth and differentiation in the bovine lens. We found that: (i) the 34 kDa protein possesses anti-phospholipase A 2 (PL/%) activity of lipocortin; (ii) in response to FGF, the anti-PLA 2 activity of this protein is enhanced whereas its phosphorylation is markedly decreased. It is suggested that the 34 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It is of note that the phosphorylation of calpactins has been suggested to regulate the level of membrane-cytoskeleton interactions (Powell and Glenney, 1987;Schlaepfer and Haigler, 1987;Crompton et al, 19881, a spatial framework thought to be involved in dramatic morphological alterations that take place as the equatorial lens epithelium begins to elongate into fiber cells (Beebe et al, 1980;Ramaekers and Bloemendal, 1981;Zelenka, 1983;Beebe and Cerrelli, 1989). It is also of note that the anti-PLAZ activity of calpactins appears to be dependent on their phosphorylation state in the equatorial epithelium (Blanquet et al, 1988(Blanquet et al, , 1990. In addition, studies have indicated that calpactins can be found in the nucleus and contain DNAbinding motifs, purportedly participating in the regulation of transcriptional activity (Jindal et al, 1991;Raynal et al, 1992;Boyko et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is of note that the phosphorylation of calpactins has been suggested to regulate the level of membrane-cytoskeleton interactions (Powell and Glenney, 1987;Schlaepfer and Haigler, 1987;Crompton et al, 19881, a spatial framework thought to be involved in dramatic morphological alterations that take place as the equatorial lens epithelium begins to elongate into fiber cells (Beebe et al, 1980;Ramaekers and Bloemendal, 1981;Zelenka, 1983;Beebe and Cerrelli, 1989). It is also of note that the anti-PLAZ activity of calpactins appears to be dependent on their phosphorylation state in the equatorial epithelium (Blanquet et al, 1988(Blanquet et al, , 1990. In addition, studies have indicated that calpactins can be found in the nucleus and contain DNAbinding motifs, purportedly participating in the regulation of transcriptional activity (Jindal et al, 1991;Raynal et al, 1992;Boyko et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Although the physiological roles of calpactins in general still remain obscure, it was suggested that these proteins might be involved in the regulation of growth and differentiation (William et al, 1988;Jindal et al, 1991;Talian and Zelenka, 1991;Boyko et al, 1994;Reutelingsperger et al, 1994). Interestingly, preliminary observations in our laboratory suggested that a bFGF-stimulatable PTPase activity confined to the equatorial epithelium of bovine lens appears to act predominantly on a calpactin-like protein (Blanquet et al, 1988(Blanquet et al, , 1990. The possibility that the phosphorylation statute of this protein may be involved in modulating fiber differentiation opens therefore an exciting area of research.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In intact cells they are substrates for the EGF [14][15][16][17] and insulin [18] receptor kinases and for pp60V"src (see [10,19] for references), and have been shown to translocate from cytoplasm to the membrane upon Ca21 treatment [20]; yet the key biological functions of the proteins are unclear. In assays in vitro, phosphorylation decreases their Ca2" affinity, decreases their ability to bind membranes, and neutralizes the phospholipase-inhibitory activity [21][22][23][24][25]. Because alterations in the N-terminal segment affect these processes [26,27], an important step in understanding the roles of these two proteins is to understand the state of the N-terminal segment and of its interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation alters calcium and phospholipid binding properties in vitro Powell and Glenney, 1987); however, the key biological effects of this modification are unclear. While many studies have demonstrated that phosphorylation of the lipocortins eliminates their PLA2 inhibitory activity, in all instances where phosphoamino acid analysis was performed, the critical site of phosphorylation was localized on serineithreonine residues (Hirata, 1981;Takagi and Ichikawa, 1987;Blanquet et al, 1988).…”
mentioning
confidence: 99%